Isolated specialist or system integrated physician - different views on sickness certification among orthopaedic surgeons: an interview study - Swartling Malin; Wahlström Rolf (BMC, 2008)
Abstract Background Sickness certification is a frequent and sometimes problematic task for orthopaedic surgeons. Our aim was to explore how orthopaedic surgeons view their sick-listing commission and sick-listing practice. Methods Semi-structured interviews with seventeen orthopaedic surgeons from five orthopaedic clinics in four Swedish counties. The focus was on the experiences of these physicians in relation to handling of sickness certification. Phenomenographic analysis was performed to reveal differences in existing views. Results The orthopaedic surgeons' views on sick-listing seemed mainly to be a consequence of how they perceived their role in the healthcare system. Three categories were found: The "isolated specialists", whose work and responsibilities were confined to the orthopaedic clinic, and did not really include sickness certification; the "orthopaedic advisers", who saw themselves mainly as advice-givers in the general health care system and perceived sickness certification as part of their job; the "system-integrated physicians", who perceived the orthopaedic clinic as one part of the healthcare system and whose ultimate goal was to get the patient well functioning in her life again with regained work ability, seeing sick-listing as one of the instruments to achieve this. Some informants described difficulties in handling conflicting opinions with patients in relation to the need for sick-leave. Conclusion Orthopaedic surgeons certify a large proportion of total sickness benefits. Some orthopaedic surgeons may certify sickness benefits sub-optimally for patients and society due to a narrow view of their role in the health care system or due to poor skills in handling discordant opinions with the patient. This problem can be addressed at the level of the individual physician and at the system level.